ISLAM DAN SEKULARISME DALAM AL-QUR’AN DENGAN METODE TAFSIR MAUDHU’I - Nur Afni Sayyidatul Majidah; Nur Rossa Kurniasih; Nurul Nissa; Rizky Anugrah (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The life of this world and the hereafter cannot be separated, for a better afterlife we must go through this world and make the best use of it. However, today there is an understanding that separates the two and assumes that real life only exists in the world so that it leaves God's values in living its life. Doing worldly things and occupying oneself with its pleasures and delights and making it the only purpose of this life, forgetting and neglecting the hereafter and not looking at the good deeds of the hereafter or paying attention to them. Therefore, this understanding must be known in order to be careful and not follow it. This study aims to determine the Qur'an's view of secularism through the maudhu'i interpretation method. Utilization of this research is expected to add insight into knowledge related to the study of the Qur'an. This type of research is library research or library research. The object of his study is verses related to secularism. The data sources that the author uses are divided into two parts, namely primary sources and secondary sources, some of the primary sources are taken from the Koran while the secondary sources are books related to secularism. This research succeeded in finding the conclusion that secularism endangers Islam because it separates religion from social and state life which in turn can lead its adherents to disbelief. Secularism separates religion from life, whereas Islam requires that every life be governed by Islamic teachings. Laws in secularism are also made by a handful of people who cannot be separated from their own interests, justice is only a hope. On the contrary, Islamic law guarantees the achievement of justice because it comes from the Most Just Substance. Implementing secularism means abandoning the best law, namely the law of Allah SWT.